Hierarchical control strategy for unbalanced voltage in an islanded microgrid - Tianyi Ma; Guangyao Cheng; Xinjun Liu (Технічна електродинаміка, 2016)
When the microgrid is running in an islanded mode, unbalanced loads result in microgrid voltage unbalance. The
voltage unbalance factor at the Point of Common Coupling (PCC) is a key parameter in measurement of microgrid
power quality. To improve microgrid power quality, many documents utilize micro-source voltage measurement results
to help adjust the unbalance factor of microgrid voltage. However, due to line impedance presence, there are
differences between micro-source output voltage and PCC voltage. Therefore, it is impossible for a micro-source to
control the unbalance factor of PCC voltage with high precision by measuring its own output voltage. Based on
equivalent circuit, the present paper analyzes the negative sequence component relationship among micro-source
output voltage, line impedance voltage drop, and PCC voltage. It further proposes a hierarchical-control-based method
to control the unbalance factor of PCC voltage with high accuracy, and analyzes the impact of secondary control delay
on system stability by root locus calculating. Finally, the control strategy is validated in an islanded microgrid system
with two micro-sources. The experimental results show the effectiveness and feasibility of the proposed control strategy. Під час роботи мікроенергосистеми (МЕ) в ізольованому режимі незбалансовані навантаження призводять до
дисбалансу напруги у ній. Фактор дисбалансу напруги у точці спільного приєднання (ТСП) є основним параметром
при вимірюванні якості електроенергії МЕ. Для підвищення якості електроенергії МЕ використовують
результати вимірювань напруги мікроджерел для врегулювання фактора дисбалансу напруги МЕ.
Проте через наявність повного вхідного опору лінії існують відмінності між вихідною напругою мікрождерела
та напругою ТСП. Тому мікроджерело не може контролювати фактор дисбалансу напруги ТСП з високою
точністю шляхом вимірювання власної вихідної напруги. На базі еквівалентної схеми у даній статті аналізуються
відношення складової оберненої послідовності між вихідною напругою мікроджерела, падінням напруги
повного вхідного опору лінії та напругою у ТСП. Також для контролю фактора дисбалансу напруги ТСП
із високою точністю пропонується метод на основі ієрархічного контролю, аналізується вплив затримки вторинного
контролю на стабільність системи. Стратегія контролю перевірялася в ізольованій мікроенергосистемі
з двома мікроджерелами. Дослідні дані показують ефективність та доцільність запропонованої
стратегії контролю. При работе микроэнергосистемы (МЭ) в изолированном режиме несбалансированые нагрузки приводят к дисбалансу
напряжения в ней. Фактор дисбаланса напряжения в точке общего присоединения (ТОП) является основным
параметром при измерении качества электроэнергии МЭ. Для улучшения качества электроэнергии МЭ
используют результаты измерений напряжения микроисточников для урегулирования дисбаланса напряжения
МЭ. Однако из-за наличия полного входного сопротивления линии существуют различия между выходным напряжением
микроисточника и напряжением ТОП. Поэтому микроисточник не может контролировать дисбаланс
напряжения ТОП с высокой точностью путем измерения собственного выходного напряжения. На основании
эквивалентной схемы в данной статье анализируется отношение составляющей обратной последовательности
между выходным напряжением микроисточника, падением напряжения полного входного сопротивления
линии и напряжением в ТОП. Также для контроля фактора дисбаланса напряжения ТОП с высокой
точностью предлагается метод на основе иерархического контроля, анализируется влияние задержки вторичного
контроля на стабильность системы. Стратегия контроля проверялась в изолированной микроэнергосистеме
с двумя микроисточниками. Опытные данные показывают эффективность и целесообразность предлагаемой
стратегии контроля.